Allegro Ma Non Troppo: ambiguidades do riso na dramaturgia de Oduvaldo Vianna Filho - Vieira, Thaís Leão (2011)
The purpose of this thesis is to approach humor as the central element on Oduvaldo Vianna Filho Vianinha s work, through the analysis of the comedies that were written in the period before the blow of 1964 (Bilbao, Via Copacabana -1957, A Mais Valia vai Acabar Seu Edgar 1960, Cia.Amafeu de Brusso - 1961) and in the post-1964 (Dura Lex Sed Lex no Cabelo só Gumex 1967, AllegroDesbundaccio ou se Martins Pena Fosse Vivo -1973). Accordingly, the main argument is that the study of his comic works help us notice that under the weight of failure and perplexity against the blow, Vianinha turns into a critic of himself and the allegoric characters of the post-blow express the feeling of the contrary, in other words, the perception of a private that is the opposite of what it should be. The way he used humor on the post-blow period revealed absurd behaviors and situations, many times derived from the tragic, expressing on the narrative style a look to themselves and to the social group they were inserted in within the consumer society.